2021
DOI: 10.1371/journal.pone.0252430
|View full text |Cite
|
Sign up to set email alerts
|

Big Five Personality Model-based study of death coping self-efficacy in clinical nurses: A cross-sectional survey

Abstract: Background Specific personality traits may affect the ability of nurses to deal with patient death. The relationship between personality and death coping self-efficacy (DCS) has rarely been investigated in the palliative care setting. In this study, we explored the associations between different personality profiles and DCS in clinical nurses from general wards and ICU. Methods A cross-sectional survey of 572 Chinese nurses was conducted between August and September 2020, by way of a self-administered questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Death-coping self-efficacy (DCS) refers to whether a nurse has the confidence to provide palliative care timely to dying patients and assist their family members, which include the confidence to evaluate needs, dealing with care problems, managing symptoms and providing information, coping with the death of a loved one and planning and preparation for burial [ 1 ]. It has always been the core goal of palliative care to allow patients to treat death with the best mentality, optimism and happiness at the end of life, and to achieve a "good death" [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Death-coping self-efficacy (DCS) refers to whether a nurse has the confidence to provide palliative care timely to dying patients and assist their family members, which include the confidence to evaluate needs, dealing with care problems, managing symptoms and providing information, coping with the death of a loved one and planning and preparation for burial [ 1 ]. It has always been the core goal of palliative care to allow patients to treat death with the best mentality, optimism and happiness at the end of life, and to achieve a "good death" [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In explaining these findings, it can be said that neurotic people usually have low emotional stability and are worried, stressed, and rushed. Still, extroverted people are bold, thrill-seeking, and emotional [12]. Therefore, it can be predicted that both groups will experience higher health anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…They present with adaptability, trustworthiness, honesty, altruism, kindness, humility, and self-sacrifice. Conscientiousness is a measure of reliability, and a person with a high conscience is competent, orderly, conscientious, purposeful, self-disciplined, and punctual [12].…”
Section: Introductionmentioning
confidence: 99%
“…Neuroticism and openness traits were high in Yazdanian et al’s study [ 28 ]. Other studies have reported that conscientiousness was the most common trait among nurses working in general wards and ICUs, and nurses having worked in a nursing position for at least one year [ 29 ].…”
Section: Discussionmentioning
confidence: 99%